OPTIMIZING THE POTENTIAL OF KRUENG RAYA RIVER FOR STRENGTHENING LOCAL ECONOMIC DEVELOPMENT AND ENVIRONMENTAL RESILIENCE: OPTIMALISASI POTENSI SUNGAI KRUENG RAYA UNTUK PENGUATAN EKONOMI LOKAL DAN KETAHANAN LINGKUNGAN - Novi Mailidarni; Badruzzaman; Zamzami; Sulaiman; Tasliati Djafar; Juliawati; Jauhari; Ilya Puryani (PT. ROCE WISDOM ACEH, 2026)
The Krueng Raya River plays a strategic role in supporting the livelihoods of surrounding communities, both as an environmental resource and as a foundation for local economic activities. However, the river’s use remains limited and not managed optimally, resulting in underdeveloped economic potential and minimal impact on community welfare. At the same time, increasing pressure on the river ecosystem from human activities and land-use changes could reduce ecological functions and heighten environmental vulnerability. This community service program aims to optimize the potential of the Krueng Raya River to strengthen local economic development while enhancing environmental resilience. The approach involves identifying river-based economic opportunities, providing community education and assistance, and promoting environmentally friendly practices for using river resources. The expected outcomes of this program include improved community capacity for sustainable river management, the development of local economic activities based on river resources, and the preservation of the Krueng Raya River’s ecological functions as part of a long-term effort to strengthen environmental resilience.